2012
DOI: 10.1080/02680513.2012.716657
|View full text |Cite
|
Sign up to set email alerts
|

One college’s use of an open psychology textbook

Abstract: The high cost of textbooks is of concern not only to college students but also to society as a whole. Open textbooks promise the same educational benefits as traditional textbooks; however, their efficacy remains largely untested. We report on one community college's adoption of a free online psychology textbook. During the fall semester, 2011, 690 students used this book. Compared to students using a traditional text in the spring of 2011, students who used the free online textbook scored higher on department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 6 publications
5
99
1
1
Order By: Relevance
“…These findings echo those of other studies that have discovered lower withdrawal rates, higher completion rates, and greater enrolment intensity following OER adoption (Hilton & Laman, 2012;Hilton, Fischer, Wiley, & William, 2016). Indeed, thirteen studies (with an aggregated sample of 119,720 students) that have investigated the impact of OER adoption on course performance found that 95% of these students have achieved the same or better outcomes when using OER Wiley et al, 2016).…”
Section: Introductionsupporting
confidence: 83%
“…These findings echo those of other studies that have discovered lower withdrawal rates, higher completion rates, and greater enrolment intensity following OER adoption (Hilton & Laman, 2012;Hilton, Fischer, Wiley, & William, 2016). Indeed, thirteen studies (with an aggregated sample of 119,720 students) that have investigated the impact of OER adoption on course performance found that 95% of these students have achieved the same or better outcomes when using OER Wiley et al, 2016).…”
Section: Introductionsupporting
confidence: 83%
“…Students have also consistently reportedparticularly in the case of open textbooks -that OER have helped them financially (Pitt, 2015). OER use has also been correlated with higher test scores and lower rates of attrition (Hilton & Laman, 2012) though it is more common to find that use of OER delivers equivalent student satisfaction and performance at massively reduced cost (Feldstein et al, 2012;Wiley et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Such freedom makes these resources especially useful for online and distance learning scenarios because online instructors and course developers can freely share, remix, and employ direct-linking to resources rather than operating within the strict limitations of fair use (Belikov & Kimmons, in press). Research into open textbooks has yielded neutral-positive results for learning outcomes, meaning that students using open textbooks generally perform as well as or better than students using restricted textbooks, and have also yielded positive results for cost savings (Bliss, Hilton, Wiley, & Thanos, 2013;Fischer, Hilton, Robinson, Wiley, 2015;Hilton & Laman, 2012;Mtebe & Raisamo, 2014;Prasad & Usagawa, 2014;Robinson, Fischer, Wiley, & Hilton, 2014;Walker, 2007), but there is need to expand the literature in the area of textbook quality and to enact a paradigmatic shift in how we think about educational resource quality assurance. This is especially pertinent for professionals in ODL as a shift to open textbooks will need to be supported by studies on resource quality to help bolster the perceived overall quality of online learning experiences.…”
Section: Literature Reviewmentioning
confidence: 99%